A Analysis of Student Mastery Levels on Composite Material Subjects in South Aceh Polytechnic Mechanical Engineering Study Program - Muhammad Anhar Pulungan; Sera Delta Tanjung (Jurnal Inotera, 2019)
Research is included into the type of descriptive study using quantitative and qualitative approaches. The research procedure includes stage 1) initial observation, 2) preparation, 3) implementation, 4) evaluation, and 5) final results. The subjects in this study were the second semester students of Mechanical Engineering Study Program, totaling 24 people. Data collection techniques used 1) test questions, 2) interviews, 3) documentation, and 4) field notes. Data analysis techniques mastery level of the material were analyzed using the percentage formula. Interview data were analyzed in stages 1) reducing data, 2) presenting data, and 3) summarizing data. Instrument documentation and field notes were analyzed narratively. The results of data analysis on the level of student mastery of composite material shows that the group of students in the category of mastery is very mastering (SM) 0 students (0%), the category of mastery mastering (M) is 9 students (23.68%), the category of mastery is less mastering (KM ) 16 students (42.11%), mastery category not mastered (TM) 13 students (34.21%). Students who mastered the mastery-1 category were 15 students (39.47%), who mastered the mastery-2 category by 22 students (57.89%), who mastered the mastery-3 category by 9 students (23.68%) and categories mastery-4 as many as 0 students (0%). Interview results obtained by some students 'mistakes in mastering composite material courses, namely a) errors in the use of formulas or concept errors, b) errors in algebraic fraction operations, c) students' lack of attention to the tests conducted, d) errors in inputting parameter values, e) errors in the operation of exponential numbers, f) errors in formulating problems in the form of formulas (mathematical modeling), and g) principle errors.